2007
DOI: 10.1016/j.jadohealth.2007.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Bullying Involvement and Perceived Family, Peer and School Relations: Commonalities and Differences Across Race/Ethnicity

Abstract: Purpose-Although bullying is recognized as a serious problem in the U.S., little is known about racial/ethnic differences in bullying risk. This study examined associations between bullying and family, peer, and school relations for White, Black and Hispanic adolescents.Methods-A nationally-representative sample (n=11,033) of adolescents in grades six to ten participated in the 2001 Health Behaviors in School-Aged Children survey, self-reporting bullying involvement and information on family, peer and school r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
282
4
31

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 406 publications
(338 citation statements)
references
References 34 publications
21
282
4
31
Order By: Relevance
“…In his early research, Olweus (1978Olweus ( , 1993 distinguished between children who bully others and those who both bully others and are victimized. These "bully victims" have been characterized as hyperactive, impulsive, and as experiencing more peer rejection, more academic difficulties, and more stressful and harsh home environments (see Schwartz, Proctor, & Chien, 2001), but represent only a small portion (1% to 12%) of students (Dulmus et al, 2006;Nansel et al, 2001;Solberg & Olweus, 2003;Spriggs, Iannotti, Nansel, & Haynie, 2007). Over the past four decades, research has also shown that many bullies are socially intelligent (Björkqvist, Österman, & Kaukiainen, 2000;Sutton, Smith, & Swettenham, 1999a, 1999b and enjoy considerable status in the peer group (Vaillancourt et al, 2003), leading to distinctions between socially marginalized and socially integrated bullies (Farmer et al, 2010).…”
Section: Different Types Of Bulliesmentioning
confidence: 99%
“…In his early research, Olweus (1978Olweus ( , 1993 distinguished between children who bully others and those who both bully others and are victimized. These "bully victims" have been characterized as hyperactive, impulsive, and as experiencing more peer rejection, more academic difficulties, and more stressful and harsh home environments (see Schwartz, Proctor, & Chien, 2001), but represent only a small portion (1% to 12%) of students (Dulmus et al, 2006;Nansel et al, 2001;Solberg & Olweus, 2003;Spriggs, Iannotti, Nansel, & Haynie, 2007). Over the past four decades, research has also shown that many bullies are socially intelligent (Björkqvist, Österman, & Kaukiainen, 2000;Sutton, Smith, & Swettenham, 1999a, 1999b and enjoy considerable status in the peer group (Vaillancourt et al, 2003), leading to distinctions between socially marginalized and socially integrated bullies (Farmer et al, 2010).…”
Section: Different Types Of Bulliesmentioning
confidence: 99%
“…Parents represent children's primary socialization agents and play a critical role in their children's social development and understanding. The bullying literature on typically developing youth indicates that peer victimization experiences are related to poor parent-child relationships (Spriggs, Iannotti, Nansel, & Haynie, 2007;Ybarra & Mitchell, 2004). Because peers have such a critical socialization role during childhood and adolescence (Brown, Eicher, & Petrie, 1986), peer relationships are likely implicated in the consideration of risks and protective processes related to victimization.…”
mentioning
confidence: 99%
“…Okulda zorbalık davranışlarının, akran ilişkileri yönünden ele alındığı bazı araştırmalarda, zorba statüsündeki ergenlerin akran grupları tarafından daha az dışlandıkları görülmüştür. Zorba grup tarafından kabul gören bu ergenlerin diğer akranları tarafından kabul edilmediklerine dair bulgular bulunmaktadır (Spriggs, Iannotti, Nansel ve Haynie, 2007). Akran grubuna ait olmanın saldırgan davranışları arttırdığı bulgusu literatür ile paralellik göstermektedir (Kobak, Cassidy, Lyons-Ruth ve Ziv, 2006;Spriggs ve ark., 2007).…”
Section: Discussionunclassified